2019
DOI: 10.1016/j.chemgeo.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of the hydrated Mg-carbonates nesquehonite and dypingite from 5 to 35 °C: Implications for CO2 storage and the relative stability of Mg-carbonates

Abstract: Hydrated Mg-carbonate minerals form during the weathering of ultramafic rocks, and 2 can be used to sequester atmospheric CO 2 to help combat greenhouse gas-fueled climate change. Optimization of engineered CO 2 sequestration and prediction of the composition and stability of Mg-carbonate phase assemblages in natural and engineered ultramafic environments requires knowledge of the solubility of hydrated Mg-carbonate phases, and the transformation pathways between these metastable phases. In this study, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 119 publications
3
61
0
1
Order By: Relevance
“…The morphology of these magnesium carbonate hydrate particles produced by talc carbonation was visualized by SEM, and the representative images are presented in Figure 1. As can be observed, the magnesium carbonate hydrate particles exhibited four different microscopic morphologies [22][23][24]. In Figure 1a, the needle-like particles were produced, and the axis diameter was in the range of 0.3-0.8 µm.…”
Section: Production Of Magnesium Carbonate Hydrate With Different Mormentioning
confidence: 93%
“…The morphology of these magnesium carbonate hydrate particles produced by talc carbonation was visualized by SEM, and the representative images are presented in Figure 1. As can be observed, the magnesium carbonate hydrate particles exhibited four different microscopic morphologies [22][23][24]. In Figure 1a, the needle-like particles were produced, and the axis diameter was in the range of 0.3-0.8 µm.…”
Section: Production Of Magnesium Carbonate Hydrate With Different Mormentioning
confidence: 93%
“…Numerous approaches to CO 2 sequestration have extensively been studied (Park and Fan, 2004;Rendek et al, 2006;Kelemen and Matter, 2008;Assayag et al, 2009;Montes-Hernandez et al, 2009;Felmy et al, 2012;Farhang et al, 2016;Noiriel and Daval, 2017). Magnesium carbonates, therefore, offer attractive possibilities for the permanent and safe geological storage of CO 2 (Hänchen et al, 2008;Ferrini et al, 2009;Ballirano et al, 2010;Harrison et al, 2019). In the MgO-CO 2 -H 2 O system at temperatures ranging from 0 to 60°C, the thermodynamically stable phases are brucite Mg(OH) 2 and magnesite MgCO 3 (Königsberger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Natural nesquehonite is associated with weathering of ultramafic rocks; besides, it is found in caves and coal mines, whereas its formation has been reported in Mg-rich mining waste stockpiles depending on the environmental conditions. [2][3][4] Recent studies showed that nesquehonite can be the product of CO 2 mineralization under low pressure conditions. [5,6] The main advantage of nesquehonite in being a potential permanent storage for CO 2 emissions is that at least 30% of its structure consists of CO 3 2−.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Nesquehonite exhibits excellent physical and chemical properties for building materials [5,6,8,15,16] and can be potentially used for industrial purposes as acoustic or insulation panels. [6] The chemical formula of nesquehonite has been proposed either as MgCO 3 •3H 2 O or as Mg (HCO 3 ) (OH)•2H 2 O [9][10][11][12][13][14] ; the second one assumes the presence of HCO 3 − and OH − in the nesquehonite structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation